2021: hackers value quality over quantity. (11th January 2022) - O'Connor, Patrick
Abstract: Reported intrusions are down, the amount of personal data exposed is down, so it's all good, right? Well yes and no… Patrick O'Connor MBCS CISSP CEH explores the good and bad of events in cyber security in 2021.